Berita dan Opini Keagamaan dalam Surat Kabar Waspada Medan - Nurman Kholis (Jurnal Lektur Keagamaan, 2014)
This study aims to reveal the news and the opinions on religious heritage in  newspaper Waspada, Medan. This study also tries to reveal the section that contains the spreading of the news and the opinion in each section. From the news and the opinions in Waspada  newspaper edition January until August 2011, the study found that there are amount news and opinion on  religious-heritage as much as 25 titles. The religious discourse in the news and the opinion consists of categories: a) history (6 titles), b) currency (1 title), c) Profiles (3 titles), d) Old Mosque (7 titles), e) Temple ( 2 titles), f) the ancient Tomb (2 titles), g) Tombstone (1 title), and h) Dance (3 titles).Keywords: Religious Heritage, News, Opinion, Waspada Newspaper